Malgré les apparences: Derrida, Lacan y el círculo (vicioso) “hermenéutico” - Fasolino, Ruben Carmine (Bollettino Filosofico, 2021)
This essay resumes some points regarding the confrontation between Derrida deconstruction and Lacan psychoanalytic theory which I have already discussed in some previous essays. The aim is to show that the intention has never been of criticizing – in the sense of refusing – the position of Lacan from Derrida point of view or, vice versa, reading Lacan through Derrida. The aim has rather been of criticizing – in the sense of discerning – Derrida deconstrucion through Lacan psychoanalytic theory and the latter through the former. The reason for that is to show that both positions state the same in different words and gestures. Keywords: Deconstruction, Hermeneutics, Letter, Psychoanalysis, Significant